Observational evidence of high methane emissions over a city in western India. (1st April 2019) - Chandra, N.; Venkataramani, S.; Lal, S.; Patra, P.K.; Ramonet, M.; Lin, X.; Sharma, S.K.
Abstract: Urban areas emit large amounts of methane (CH4 ) to the atmosphere from landfills, wastewater treatment facilities, waste dump and consumption and infrastructure of natural gas. CH4 emissions from India are increasing, especially from the urban regions due to fast socioeconomic developments. Therefore, the total emissions of all greenhouse gases (GHGs) from these regions need to be continuously monitored. However, the systematic measurements of GHGs at urban regions in India are lacking to record the current emission scenarios. We have initiated high-frequency measurements of atmospheric CH4 dry-air mole fraction (DMF), along with carbon dioxide (CO2 ) and carbon monoxide (CO) at Ahmedabad, a representative urban site in western India, using laser-based cavity ring down spectrometer from July 2014 to July 2015. The time series analysis suggests that the study region exerts very high emissions of CH4, and the tracer-tracer correlations of CH4 :CO2 and CH4 :CO indicate that the combustion related anthropogenic and fugitive sources are the two main sources of CH4 in the study region. The seasonally high (low) values of CH4 DMF are observed during October–February (May–August) months, and the diurnally high (low) CH4 are observed during midnight (afternoon) hours. We compute the total CH4 emission from Ahmedabad to be ∼58 ± 16 Gg for the year 2014, which is ∼45% higher than the EDGARv4.2 FT2010 inventory estimates. The observed time series are compared to simulations from two global atmospheric chemistry-transport models (i.e. ACTM and LMDzINCA). Both of the models perform very well in simulating the seasonal cycle of CH4 when the afternoon mean observations are used but fail to simulate the evening to mid-night build-up in CH4 owing to coarse resolutions of the global models and limitations in capturing the dynamical and physical processes in the boundary layer. Highlights: Measurements of CH4 are made at the city of Ahmedabad, India along with CO2 and CO. These measurements are used to infer GHGs emission characteristics for the city. Combustion and fugitive anthropogenic sources are found to be dominant for CH4 . Estimated CH4 emission is found to be higher than the EDGAR inventory over the region. Two global models are used to explain the observed seasonal variations in CH4 .